A structurally characterised redox pair involving an indigo radical: indigo based redox activity in complexes with one or two [Ru(bpy)2] fragments. Issue 15 (4th April 2017) - Chatterjee, Madhumita; Mondal, Prasenjit; Beyer, Katharina; Paretzki, Alexa; Kaim, Wolfgang; Lahiri, Goutam Kumar
Abstract : Various radical intermediates of the non-innocently behaving dehydroindigo ligand were characterized by EPR, spectroelectrochemistry and structure analysis. Abstract : The reaction between indigo, H2 Ind, and {Ru(bpy)2 (EtOH)2 } 2+ in EtOH/NaOH produced the compounds [Ru(bpy)2 (HInd)]ClO4 [1 ]ClO4, rac -{[Ru(bpy)2 ]2 (μ-Ind)}(ClO4 )2 [2 ](ClO4 )2, and meso -{[Ru(bpy)2 ]2 (μ-Ind)}(ClO4 )3 [2 ](ClO4 )3, which were structurally characterised, the latter as the first stable, isolable radical complex of indigo. The redox pair2 2+ /2 3+ showed little structural difference, as confirmed using DFT calculations. The redox series1 n and2 n were investigated using voltammetry and spectroelectrochemistry (EPR, UV-vis-NIR). Remarkably, the EPR results for1, 1 2+, 2 + and2 3+ revealed mostly ligand based spin in ruthenium(ii ) complexes of the indigo-derived radical ligands HInd˙ 2−, HInd˙, Ind˙ 3− and Ind˙ −, in agreement with the DFT calculated spin densities. The dominance of the frontier orbitals by the metal-stabilised indigo chromophore was also confirmed via the TD-DFT based assignment of near-infrared absorptions as intra-indigo or ligand-to-ligand charge transfer transitions.